Exendin-4 regulates endoplasmic reticulum stress to protect endothelial progenitor cells from high-glucose damage. (June 2020) - Yang, Yong; Zhou, Yong; Wang, Yiyong; Wei, Xianglong; Wang, Tingzhong; Ma, Aiqun
Abstract: Background: High glucose affects the function of endothelial cells by increasing oxidative stress. Studies have found that exendin-4 can improve wound healing in diabetic mice and mice with normal blood glucose. However, the mechanism of exendin-4 in endothelial progenitor cells under high-glucose condition has not been fully elucidated. Methods: Diabetic mouse models were established to investigate the effects of exendin-4 on endothelial progenitor cells in diabetic mice. Serum superoxide dismutase (SOD) and malondialdehyde (MDA) were determined by WST-8 and thiobarbituric acid (TBA) colorimetry, respectively. Cell viability, apoptosis and reactive oxygen species (ROS) were detected by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and flow cytometry. Gene and protein expressions were determined by Quantitative reverse transcription PCR (qRT-PCR) assay and Western blot (WB). Results: The results showed that in diabetic mice, exendin-4 did not affect blood glucose or body weight, moreover, it improved aortic diastolic function, increased SOD activity and down-regulated malondialdehyde (MDA) level in the mice. In addition, exendin-4 also increased endothelial progenitor cell (EPCs) viability and reduced cell apoptosis through inhibiting p38 MAPK pathway and reducing endoplasmic reticulum stress and ROS. Conclusion: Exndin-4 can alleviate diabetes-caused damage to mice, moreover, it reduced endoplasmic reticulum stress and ROS through inhibiting p38 MAPK pathway in MPCs cells under high-glucose condition, thus increasing cell viability and reducing cell apoptosis. Highlights: High glucose destroys cell function. ER stress causes cell damage. Exndin-4 inhibited p38 MAPK pathway.